2019
DOI: 10.3390/nu11020287
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Profiling Is Needed to Improve the Nutritional Quality of the Foods Labelled with Health-Related Claims

Abstract: Health-related claims on food products influence consumers and their food preferences. None of the European countries have restricted the use of health claims to foods of high nutritional quality despite the regulatory background provided by the European Union in 2006. We evaluated the nutritional quality of foods labelled with claims available in the Slovenian market using two nutrient profile models—Food Standards Australia New Zealand (FSANZ) and European World Health Organization Regional office for Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 20 publications
(32 reference statements)
0
33
0
Order By: Relevance
“…In this study we found that 56% of all beverage front-face items available from vending machines is of lower nutritional quality. This proportion is slightly higher when compared to the beverages available in the Slovenian food supply, where 50% as was shown in a previous study (22). A recent international comparison (23) showed considerable potential for improving nutritional quality for beverages.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In this study we found that 56% of all beverage front-face items available from vending machines is of lower nutritional quality. This proportion is slightly higher when compared to the beverages available in the Slovenian food supply, where 50% as was shown in a previous study (22). A recent international comparison (23) showed considerable potential for improving nutritional quality for beverages.…”
Section: Discussionmentioning
confidence: 57%
“…They use the Food Standards Australia New Zealand (FSANZ) Nutrient Pro ling Scoring Criterion model (21) to determine the eligibility of foods and beverages to carry health claims, meaning that only foods with better nutritional quality are allowed to carry health claims. A recent study in Slovenia (22) also evaluated the nutritional quality in food supplies based on the FSANZ model and found that 50% of available beverages in food stores are of lower nutritional quality. The aim of our study was to analyse the variety and nutritional quality of beverages available in vending machines placed in social and health care institution in Slovenia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Slovenian branded foods dataset (CLAS, Composition and Labelling Information System) [31] was used for this analyses. In brief, the CLAS cross-sectional data on the composition of prepacked foods in the Slovenian food supply were collected during January-February 2015 in Ljubljana, Slovenia.…”
Section: Food Database Product Categorization and Nutritional Composmentioning
confidence: 99%
“…We did not calculate percentage for overall categories or for parent categories, since the study was conducted only on selected food categories, and therefore our sample of foods is not representative of the overall market of branded foods. Sales weighted proportion of healthier products was also calculated based on each product's 12 month sales data, which were provided by retailers, as described previously [31].…”
Section: Data Processing and Statistical Analysesmentioning
confidence: 99%